Pastoralist decisions to participate in livestock marketing systems during drought seasons: evidence from kenyan arid and semi-arid regions - S. Wagura Ndiritu; Castro Ngumbu Gichuki (Pastoralism, 2025)
Pastoralist households in Kenya’s arid and semi-arid lands (ASALs) rely heavily on livestock trade for livelihoods and income. Between 2021 and 2023, the region experienced its worst drought in four decades, marked by six consecutive failed rainy seasons. This study investigates the factors influencing pastoralists’ choice of livestock market channels during this period, focusing on the effects of drought, conflict, and livestock production systems. It also examines how different sources of livestock market information shape trading decisions. Data were collected from 1,053 households using a multistage sampling approach. Analytical methods included Multivariate Probit (MVP) regression and Classification and Regression Tree (CART) analysis. Findings reveal that informal networks, especially neighbours and family, were the most influential sources of market information. In contrast, formal channels such as mobile phone calls and radio had limited impact. Households affected by drought were more likely to sell steers through butcher outlets, reflecting urgent liquidity needs. Conflict significantly reduced participation in local markets, highlighting how insecurity limits access. Across all livestock types, namely steers, heifers, bulls, cows, sheep, and goats, pastoralists engaged in multi-channel marketing strategies shaped by herd size, household demographics, and external shocks. These results underscore the need to strengthen both traditional and digital market information systems that provide timely, localized livestock market intelligence. Supporting livestock marketing cooperatives and Common Interest Groups (CIGs) is also vital to improving coordination and bargaining power. Such interventions are essential for enhancing resilience, market participation, and economic inclusion in Kenya’s drought-prone pastoralist areas.